Programa Frutos da Terra: Um agente divulgador da cultura musical regional - REIS, Martha Antonia dos Santos (2009)
This study is the result of observation of the television Fruit of the Earth, regional character, which is being produced in Goiania, twenty-five consecutive years. Achieving the overall goal of making a critical analysis and reflective linking the program and its regional proposal in the context of globalized society Goias, and the implications assigned to this context, they acquired this registration form, in which they are exposed to exploitation and Goias indigenous culture, especially music. Therefore, considerations are made on the regional cultural events that the program airs, including traditional and particularly the music, in the process of globalization, including the issue of cultural hybridity and cultural specificities of identifications in the news. The study is systematic in three chapters, s endo that makes each chapter a specific approach, based on the thought of Edgar Morin, the complexity. A reflection on the program Fruit of the Earth gives up way of thinking fragmented portnato, do not take the object apart from its context. It was observed, and the program Fruit of the Earth for a period of eighteen months, was considered the responses obtained in the interviews, we sought in the theoretical studies by social theorists - Hall, Bauman and Canclini - and researchers in the field music - Ulhôa, Nepomuceno and Pimentel. These agents have cultural enlightening replies to the questions that arise during the research. The procedures are found in each chapter of the research. In the first chapter, the discourse is presented by globalization and its issues. The second is devoted exclusively to country music roots, its origin, the transformation in that song now, considering the result of hybridity and cultural reflection of the identifications of Goias. The third chapter presented in detail, the program. It presents the history of the program, a detailed description of some recordings of that program and a summary of the opinions of the individuals: artists, viewers and program staff. In this chapter the reader is shown the importance of the fruits of the earth for society Goiana, since it proposes the recovery, preservation and indigenous culture of Goiás